Labyrinth - Kapustin, Petr (project baikal, 2018)
The phenomenon of the labyrinth in architecture and culture is viewed together with its origin, typology, meanings and mythopoetic content. The image of the labyrinth goes through the centuries of architectural history, still remaining a virtual hero without incarnation, existing at the boundaries of everyday life.